Interview with Bangeswar Roy, founder of Communist Party in Dhaka (daughter Tania Pal helped him during the interview), interviewed by Kabir in Gouhati, Assam - Kabir, Shahriar.
Interview with Bangeswar Roy, founder of Communist Party in Dhaka (daughter Tania Pal helped him during the interview), interviewed by Kabir in Gouhati, Assam.